Los límites de la población humana - Segura Rodríguez, Carlos (2013)
After the Second World War we have seen how the human population is growing continuously. The present paper wants to show that if we need more and more resources to maintain the welfare of our society in some moment we could overcome the physical capacity of our planet. In this way, there should been some naturals or socials conditionings that constraint the future increase of the population and it would be recommended to use adequate demographic controls to diminish the consequences of such conditionings over the social wellbeing.